Immunotherapies in MuSK-positive Myasthenia Gravis; an IgG4 antibody-mediated disease - Vakrakou, Aigli G.; Karachaliou, Eleni; Chroni, Elisabeth; Zouvelou, Vasiliki; Tzanetakos, Dimitrios; Salakou, Stavroula; Papadopoulou, Marianna; Tzartos, Socrates; Voumvourakis, Konstantinos; Kilidireas, Constantinos; Giannopoulos, Sotirios; Tsivgoulis, Georgios; et al. (Frontiers in Immunology, 2023)
Muscle specific kinase (MuSK) Myasthenia Gravis (MG) represents a prototypical antibody-mediated disease characterized by predominantly focal muscle weakness (neck, facial and bulbar muscles) and fatigability. The pathogenic antibodies mostly belong to the immunoglobulin subclass (Ig)G4, a feature attributing them specific properties and pathogenic profile. On the other hand, acetylcholine receptor (AChR) MG, the most prevalent form of MG, is characterized by immunoglobulin (Ig)G1 and IgG3 antibodies to the AChR. IgG4 class autoantibodies are impotent to fix complement and only weakly bind Fc-receptors expressed on immune cells and exert their pathogenicity via interfering with the interaction between their targets and binding partners (e.g. between MuSK and LRP4). Cardinal differences between AChR and MuSK-MG are the thymus involvement (not prominent in MuSK-MG), the distinct HLA alleles, and core immunopathological patterns of pathology in neuromuscular junction, structure, and function. In MuSK-MG, classical treatment options are usually less effective (e.g. IVIG) with the need for prolonged and high doses of steroids difficult to be tapered to control symptoms. Exceptional clinical response to plasmapheresis and rituximab has been particularly observed in these patients. Reduction of antibody titers follows the clinical efficacy of anti-CD20 therapies, a feature implying the role of shortlived plasma cells (SLPB) in autoantibody production. Novel therapeutic monoclonal against B cells at different stages of their maturation (like plasmablasts), or against molecules involved in B cell activation, represent promising therapeutic targets. A revolution in autoantibody-mediated diseases is the pharmacological interference with the neonatal Fc receptor, leading to a rapid reduction of circulating IgGs (including autoantibodies), an approach already suitable for AChR-MG and promising for MuSK-MG. New precision medicine approaches involve Chimeric autoantibody receptor T (CAAR-T) cells that are engineered to target antigen-specific B cells in MuSK-MG and represent a milestone in the development of targeted immunotherapies. This review aims to provide a detailed update on the pathomechanisms involved in MuSK-MG (cellular and humoral aberrations), fostering the understanding of the latest indications regarding the efficacy of different treatment strategies.